2016
DOI: 10.1021/acs.bioconjchem.6b00632
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Functional Groups on Bioactive Supramolecular Glycopeptide Nanofibers for Differentiation of Mesenchymal Stem Cells (MSCs) to Brown Adipogenesis

Abstract: Spatial organization of bioactive moieties in biological materials has significant impact on the function and efficiency of these systems. Here, we demonstrate the effect of spatial organization of functional groups including carboxylate, amine, and glucose functionalities by using self-assembled peptide amphiphile (PA) nanofibers as a bioactive scaffold. We show that presentation of bioactive groups on glycopeptide nanofibers affects mesenchymal stem cells (MSCs) in a distinct manner by means of adhesion, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Notably, glycosylation facilitates hierarchical assembly of various natural protein-based structures, including acetylcholine receptors, flagella, and mucinous liquid crystals [20][21][22] . Peptide-based nanofibers modified with carbohydrates are finding increasing use as biomaterials for various applications, including growth factor delivery, lectin recognition, cell binding, and tissue regeneration [23][24][25][26][27][28][29][30] . Yet, the influence of glycosylation on synthetic peptide self-assembly has received only limited attention focused primarily on hydrogel formation, nanofiber morphology, and nanofiber solubility 31,32 .…”
mentioning
confidence: 99%
“…Notably, glycosylation facilitates hierarchical assembly of various natural protein-based structures, including acetylcholine receptors, flagella, and mucinous liquid crystals [20][21][22] . Peptide-based nanofibers modified with carbohydrates are finding increasing use as biomaterials for various applications, including growth factor delivery, lectin recognition, cell binding, and tissue regeneration [23][24][25][26][27][28][29][30] . Yet, the influence of glycosylation on synthetic peptide self-assembly has received only limited attention focused primarily on hydrogel formation, nanofiber morphology, and nanofiber solubility 31,32 .…”
mentioning
confidence: 99%
“…Tekinay and Guler explored the effect of different spatial arrangements of displayed carboxy, amine, and glucose groups on peptide amphiphile (PA) nanofibers on the differentiation of mesenchymal stem cells (MSCs). [115] Four peptide amphiphiles ( An innovative application of multivalent display on assembled peptide scaffolds for regenerative medicine has been recently reported that targets denatured collagen (dColl) by displaying a collagen hybridizing peptide (CHP). [58] Collagen is the most abundant protein in mammals playing crucial roles in cellular activities such as proliferation, differentiation, and regeneration.…”
Section: Other Chemical Signals For Tissue Engineeringmentioning
confidence: 99%
“…Chemical structures of Tekinay and Guler's peptide amphiphiles. [115] Black is the lauryl alkyl tail, blue is the GAVV β-sheet motif, red is Glu, magenta is Lys, and green is Ser(OGlc) F I G U R E 9 A, Chemical structure of a collagen hybridizing peptide (GPO) 9 conjugated to the β-sheet self-assembling (FKFE) 2 peptide. B, Schematic representation of the self-assembled bilayer of (FKFE) 2 presenting the collagen hybridizing peptide in a multivalent array.…”
Section: Vaccines and Immunomodulatory Materialsmentioning
confidence: 99%
“…One emerging application of glycopeptides is to create nanomaterials that can mediate cell adhesion or activate cell signaling events by interacting with carbohydrate-binding receptors [87,88,89]. For example, Guler and co-workers used glycopeptide amphiphiles to fabricate glycosaminoglycan (GAG)-like nanomaterials.…”
Section: Moving Beyond Peptides As the Functional Ligandmentioning
confidence: 99%
“…The same group also created an extracellular matrix (ECM)-mimicking scaffold using glycopeptide amphiphiles, which enhanced MSC adhesion. By altering the presentation of different functional groups, these scaffolds could induce differentiation of MSCs into brown adipocytes [89]. Additionally, they developed a self-assembled mannosylated peptide amphiphile decorated with antigen-mimetic GM3-lactone molecules as the basis for vaccines that target dendritic cells and induce their maturation [87].…”
Section: Moving Beyond Peptides As the Functional Ligandmentioning
confidence: 99%